Traditional and Non-Traditional Risk Factors of Acute Coronary Syndrome in Young Women: Evidence from the ANCORS-YW Study - Ibdah R; Al-Nusair M; Abuhalimeh R; Mahmoud SA; Laswi B; Rawashdeh S; Hamoudeh A; Kheirallah KA (International Journal of Women's Health)
Rasheed Ibdah,1,* Mohammed Al-Nusair,1,* Raghad Abuhalimeh,2 Saad A Mahmoud,1 Bushra Laswi,1 Sukaina Rawashdeh,1 Ayman Hamoudeh,3 Khalid A Kheirallah4 1Division of Cardiology, Department of Internal Medicine, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2School of Medicine, University of Jordan, Amman, Jordan; 3Department of Cardiology, Istishari Hospital, Amman, Jordan; 4Department of Public Health and Community Medicine, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan*These authors contributed equally to this workCorrespondence: Khalid A Kheirallah, Jordan University of Science and Technology, P. O.Box 3030, Irbid, 22110, Jordan, Email kkheiral@gmail.comPurpose: Young women are at risk of acute coronary syndrome (ACS). They represent a unique population exposed to traditional cardiovascular risk factors and female sex-specific, non-traditional risk factors. The current study aimed to describe traditional and non-traditional risk factors of ACS in young women from the Middle East.Patients and Methods: The present study used data from the Jordanian, nationwide, multicenter, case-control study, ANCORS-YW. Bivariate analyses and logistic regression models were used to predict independent risk factors of ACS using adjusted odds ratios (AOR) and 95% confidence intervals (CI).Results: The study included 572 young women (≤ 50-years) with a median age of 45-years, divided into an ACS group (n=154, 26.9%) and a control group with no atherosclerotic cardiovascular disease (n=418, 73.1%). The most common presentation of ACS was non-ST-elevation ACS (n=98, 64%). The ACS group, compared to control group, had higher proportions of type-2 diabetes (41.6%vs.11.7%, p< 0.001), hypertension (53.9%vs.23.4%, p< 0.001), tobacco use (37.7%vs.24.2%, p=0.001), family history of cardiovascular disease (53.2%vs.23.4%, p< 0.001), metabolic syndrome (14.3%vs.2.4%, p< 0.001), and preterm delivery (24.7%vs.16.7%, p=0.032). ACS group had nonsignificantly greater proportions of hypertensive disorders of pregnancy (29.2%vs.22.7%, p=0.109) and gestational diabetes (15.6%vs.10.3%, p=0.081). Multivariable logistic regression analyses identified five independent predictors of ACS: type-2 diabetes (AOR, 95% CI: 3.45, 1.98─5.99), family history of cardiovascular disease (3.33, 2.15─5.17), tobacco use (2.01, 1.26─3.21), hypertension (1.72, 1.07─2.78), and metabolic syndrome (4.35, 1.72─11.03).Conclusion: Modifiable risk factors play an important role in ACS risk among young women. Efforts should be made to improve primordial and primary prevention in this population.Keywords: cardiovascular, female, ischemic heart disease, prevention, myocardial infarction